Spotlight on the Corneal Back Surface Astigmatism: A Review - Patel S (Clinical Ophthalmology, 2021)
Sudi Patel,1 Larysa Tutchenko2 1“Svjetlost” Speciality Eye Hospital, School of Medicine, University of Rijeka, Zagreb, Croatia; 2Kyiv City Clinical Ophthalmological Hospital “Eye Microsurgical Center”, Kyiv, UkraineCorrespondence: Sudi Patel Heinzelova 39, Zagreb, 10000, CroatiaEmail drsudipatel1@gmail.comAbstract: Recent evidence indicates that the corneal back surface astigmatism (CBSA) contributes to the refractive state of the eye in cataract surgery, especially with the implantation of toric intraocular lenses. But this has been met with some scepticism. A review of key studies performed over the past three decades shows that the mean CBSA power ranges from 0.18(± 0.16)D to 1.04(± 0.20)D. The clinical assessment of CBSA is problematic. There is poor agreement between the current automated systems for assessment of CBSA and it is assumed that these systems directly measure the CBSA. But CBSA cannot be measured directly in vivo. A historical review of methods used to quantify the curvature of the posterior corneal surface reveals that CBSA estimated by current systems is based on values for corneal front surface astigmatism, corneal refractive index, central corneal thickness, corneal thickness at peripheral locations and the exact distance between the corneal apex and each one of these peripheral locations. Doubts and errors in these values, coupled with the precise details of the algorithm incorporated to estimate CBSA, are the likely sources of the lack of agreement between current systems. These systematic errors cloud the assessment of CBSA. Mean CBSA may be low, but it varies from case to case. There is a clear need for a realistic, practical procedure for clinicians to independently calibrate systems for estimating CBSA. This would help to reduce uncertainty and the discrepancies between instruments designed to measure the same parameter.Keywords: cornea, back surface, astigmatism, radius, thickness, refractive index